PERANAN LATAR MEMBENTUK WATAK TOKOH UTAMA NOVEL SARASWATI SI GADIS DALAM SUNYI KARYA AA. NAVIS - Kartini, Kartini; Priyadi, Antonius Totok; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractNovel Saraswati The Girl in the Silence told about a girl that dumb and deaf but never give up to keep her life. The problem of this thesis are: 1) the role of place to crate main characteristic, 2) the role of time to create main characteristic, 3) the role of sociality to create main characteristic, 4) Implementation plant of research result of novel Saraswati The in the Silence of AA. navis to study language and literature of Indonesia in the class. This research is useful in theoretical and practice. The theory of this thesis is understanding, novel element?s building, character, and cracterization, background, plot, the role of background, and learning literature. This thesis use descriptive method that is qualitative with structural approach. Based on the result of data analisys on the novel Saraswati The Girl in the Silence from AA. Navis: 1) the  role of background to create main characteristic (a) the role of place (b) the role of time (c) the role of sociality, (d) the implementation plan of research result of novel Saraswati The Girl in the Silence from AA. Navis to study language and literature of Indonesia in the class. The result of this story is suggested to researcher from AA. Navis others, another researcher that will use structural the role of background approach.Keywords: the role of the background, novel, Saraswati The Girl in the Silenc